Автоматизированная система принятия решения о качестве непрерывно-литой заготовки: методики улучшения и сегментации изображения непрерывно-литой заготовки - Мацко, И. И.; Логунова, О. С. (НТУ "ХПИ", 2011)
Рассмотрено описание автоматизированной системы принятия решения о качестве непрерывно-литой заготовки. Приведены схема классификации изображений серных отпечатков для автоматизированной системы оценки качества и методика улучшения и сегментации изображения.

Description of the automated decision-making system of continuously cast billets quality is considered. Presented the classification scheme of sulfur prints images for automated quality assessment system and technique for images improving and segmentation.
Automated decision-making system of continuously cast billets quality: technique for continuous-casted billets images improvement and segmentation
Keywords: классификации изображений; серные отпечатки; металургические предприятия; менеджмент качества; classification scheme; automated decision-making system